Student's musical creativity and the role of teachers - a study compositions written for the Music Olympiad - Rotar Pance, Branka (Muzikološki zbornik, 2017)
Creativity is the focus of research in various areas. The present paper focuses on creativity in music and the role of the teacher in stimulating and developing it in an individual%s musical development. It highlights the importance of evaluating musical ideas, the creative process and final products. The Music Olympiad involves a presentation of competitors own compositions. In the research, we analysed the characteristics of the compositions written for and performed at the first three Slovene Music Olympiads
Keywords: analize; Glasbena olimpijada; glasbena ustvarjalnost; učenci; učitelji glasbe; vrednotenje